Risk Analisys of Palm Sugar Processing as a Local Leading Product in Mamuju Regency - Dewi Purnamasari, Sri; Rahman, Syamsul; Ibrahim, Helda (Tarjih : Agribusiness Development Journal, 2025)
The palm sugar processing industry has significant economic potential as a leading local product; however, it faces various challenges that may hinder sustainability. This study aims to identify the risks encountered by palm sugar businesses in Mamuju Regency and to analyze their severity levels. The research focuses on uncertainties arising from internal and external factors, including raw material availability, production processes, marketing, financial access, and environmental and social aspects. This study employed a descriptive-exploratory method with a mixed-methods approach. Data were obtained through semi-structured interviews, observations, and closed-ended questionnaires involving eight purposively selected respondents. The analysis applied the Risk Matrix, with scores calculated as the product of probability and impact. Risks were then categorized into four levels: low, medium, high, and extreme. Data validity was strengthened through source triangulation and expert judgment from academics and related institutions. The findings identified 13 major risks. Extreme risks included reduced sap supply during the dry season (score 16) and declining market demand (score 20). High-level risks involved equipment damage, price fluctuations, limited access to capital, and extreme weather. Medium risks included inconsistent sap quality, adulteration of raw materials, and conflicts among tappers. Low-level risks were related to delayed payments and workplace accidents. The study concludes that external risks are more dominant than internal risks in determining business sustainability. Comprehensive mitigation strategies are therefore required, including equipment modernization, quality standardization, market diversification, process innovation, and improved access to capital, to enhance the competitiveness of palm sugar as a leading local product.